Ethics of Research Involving Human Subjects: The Brazilian Experience - Hossne, William Saad [UNESP]; de Freitas, Corina Bontempo Duca (Springer Nature, 2010)
Human experimentation cannot be analyzed in isolation because many forces shape social interaction - man’s quest for knowledge and mastery, his willingness to risk human life, and his readiness to delegate authority and to rely on professional judgment (Katz 1972). It was man’s capacity for seeking justice that made ethics committees possible, while at the same time it was man’s capacity for deceiving people that made ethics committees necessary (Ramsey 1982, p. 533). As Raul Hilberg wrote in The Destruction of the European Jews, “If the world was so shocked at what it discovered to be the extremes to which experimental medicine would go, it has yet to condemn the method or find the means to control it” (Hilberg 2003). From our point of view, the right choice is to control experimentation on human beings.
Keywords: Brazilian Institute; Committee Member; Indigenous People; Institutional Research Ethic Committee; Surrogate Decision Maker